Smart manufacturing: its challenge and future implementation in Malaysia / Muhammad Hazrie Ibrahim - Muhammad Hazrie , Ibrahim (2017)
Smart manufacturing, which is also known as a fourth revolution in the manufacturing industry have been identified as the way forward for Malaysia industries to improve competitiveness through the introduction of cutting-edge ICT technologies and the convergence with the existing manufacturing technologies. However, the blueprint of these evolutions, technological borders and the application of framework are not yet specified. Therefore, the adoption of this paradigm change still requires more research to further analyze the potential challenge and implementation of Industry 4.0 and Smart Manufacturing in Malaysia. Towards this goal, this paper seeks to review the implementation of smart manufacturing in other developed countries such as Germany, USA, Japan and Republic of Korea by identifying strategies established to support the implementation of smart manufacturing in their respective countries. Our next objective is to explore the feasibility of implementing Industry 4.0 in manufacturing companies in Malaysia by identifying the potential challenge of implementation, as well as the opportunities and trade-offs that these companies would expect from an implementation of these integrated technologies. Keywords: Smart manufacturing, Industry 4.0, competitiveness, challenges, implementation